1977
DOI: 10.1017/s0033291700029317
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal of body perception disturbance in anorexia nervosa

Abstract: SYNOPSIS Previous research has suggested that patients suffering from anorexia nervosa tend to overestimate their body size, whereas normal females tend to be very accurate in this respect. This paper presents the results of further investigations of body perception amongst anorexic and normal females. The results, in contrast to earlier findings, indicate no such difference between groups. Detailed analysis of the data, however, points to the likelihood of certain differences between the present group of anor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
2
2

Year Published

1977
1977
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(78 citation statements)
references
References 10 publications
10
64
2
2
Order By: Relevance
“…In other studies (but using widely different methods), BSE results were found to be related to the duration and severity of illness, psychosexual immaturity, dieting tendencies, and several psychopathological variables (Button, Fransella, & Slade, 1977;Casper, Halmi, Goldberg, Eckert, & Davis, 1979;Garner, Olmsted, Bohr, & Garfinkel, 1982;Gar- ner, Garfinkel, Stancer, & Moldofsky, 1976;Garfinkel, Moldofsky, Gardner, Stancer, & Coscina, 1978;Goldberg, Halmi, Casper, Eckert, & Davis, 1977;Meermann, Vandereycken, & Napierski, 1986;Strober, Goldenberg, Green, & Saxon, 1979;Strober, 1981;Thompson, Penner, & Altabe, 1990). Our study, however, could not determine any noteworthy correlations between the results of the different video distortion tasks and general psychological complaints and clinical variables.…”
Section: Discussionmentioning
confidence: 88%
“…In other studies (but using widely different methods), BSE results were found to be related to the duration and severity of illness, psychosexual immaturity, dieting tendencies, and several psychopathological variables (Button, Fransella, & Slade, 1977;Casper, Halmi, Goldberg, Eckert, & Davis, 1979;Garner, Olmsted, Bohr, & Garfinkel, 1982;Gar- ner, Garfinkel, Stancer, & Moldofsky, 1976;Garfinkel, Moldofsky, Gardner, Stancer, & Coscina, 1978;Goldberg, Halmi, Casper, Eckert, & Davis, 1977;Meermann, Vandereycken, & Napierski, 1986;Strober, Goldenberg, Green, & Saxon, 1979;Strober, 1981;Thompson, Penner, & Altabe, 1990). Our study, however, could not determine any noteworthy correlations between the results of the different video distortion tasks and general psychological complaints and clinical variables.…”
Section: Discussionmentioning
confidence: 88%
“…Norris (1984) found a significant correlation between the degree of overestimation after mirror confrontation and progress in treatment, in patients with anorexia nervosa, as measured on a specially devised rating scale. In addition, research has indicated that overestimation of body size may actually predict relapse after treatment in patients with anorexia nervosa (Button et al, 1977;Crisp & Kalucy, 1974). Similarly, in patients with bulimia nervosa, body size overestimation has been shown to be associated with less progress in treatment (Norris, 1984) and overestimation of hip and waist size has been found to decrease after treatment in patients with bulimia nervosa (Birtchnell et al, 1985).…”
Section: Relevance Of Body Size Estimationmentioning
confidence: 99%
“…Thus, results obtained by independent investigators with two different objective measures of body size perception have indicated overestimation of self-size in anorexia nervosa to be associated with poor prognosis (11,32,96), psychopathology (35), vomiting (11,22,32), and rapid weight gain (40). As yet unresolved are an understanding of the origins and stability of these perceptual disturbances and of the heterogeneity of body perceptions between patients with eating disorders.…”
Section: Body Imagementioning
confidence: 99%